SAPTONO DALAM MELESTARIKAN DAN MENGEMBANGAN KARAWITAN TRADISI SURAKARTA - Utami Ciptaningsih; Zulkarnain Mistortoify (Institut Seni Indonesia Surakarta, 2022)
This qualitative research is about the figure of Saptono in the world of classical Surakarta-style karawitan. Saptono is a skilled musician in mastering the repertoire of gendhing and ricikan in all types of Javanese Surakarta-style gamelan. Apart from being a former lecturer at ISI Yogyakarta, he also serves as a gamelan musician at the Surakarta Kasunanan Palace. High loyalty and musical virtuosity made Saptono appointed Kanjeng Raden Riyo Aryo (K.R.R.A) Saptonodiningrat and given a special task as tindhih of gamelan musicians at the Surakarta Kasunanan Palace. Two basic questions arise about how Saptono creative activities maintain the continuity of the Surakarta style musical and what reasons encourage him to do these activities. Based on these two questions, it is known that all forms of loyalty to the Surakarta Kasunanan Palace are shown by Saptono by utilizing all of his musical potential in creating classical Surakarta style gendhing, which is specifically dedicated to King Paku Buwana XIII. Saptono dedication to the development of karawitan to the wider community is shown through his willingness to become a music teacher at home and abroad, become a courtier of musicians at the Kasunanan Surakarta Palace, and become a driving force for the Muryoraras art community as a meditation association with Javanese gamelan instruments.